Discrete Event Simulation using DELMIA: Production optimization for small and mid-sized enterprises using the DES software DELMIA - Malmsjö, Gustaf; Nilsson, Joel (My University, 2022)
In today’s industry, cost-efficient processes are key to maintaining a company’s prof itability and competitiveness. With the technological enhancement in industry, simulation software has proven to be a quick and cost-efficient method of virtu ally observing and analyzing processes. This enables the conduction of analysis and testing, without interfering with the actual operation. This thesis aims at evaluating how discrete event simulation (DES) software, with practical use in DELMIA, can aid in performing improvement work of a production line, as well as determining the resource demand to use DELMIA for small and mid-sized enterprises (SMEs). To evaluate the practical use of DELMIA in industry, the production line X-line3 at Axelent AB was replicated and analyzed. Interviews and stopwatch time stud ies, along with an improvement generation phase, resulted in various improvement proposals for the production line. Results of using DELMIA to implement the im provement proposals show that a proposal of fully automating the line as well as adding a fixture and adjusting machine parameters will create the largest through put increase of 283 %. The proposal focuses on elevating constraints, and whenever a new constraint was identified, the process was iterated until a satisfactory result was achieved or until limited by outside factors. The study shows that DELMIA and DES software are great tools to provide statistics to gain an overall view of a production station, line, or entire factory, which can create value for SMEs in their processes.
Keywords: simulation, simulation software, DELMIA, DES, production, improvement, SME